High Density, Double-Sided, Flexible Optoelectronic Neural Probes With Embedded μLEDs - Reddy, Jay W.; Kimukin, Ibrahim; Stewart, Luke T.; Ahmed, Zabir; Barth, Alison L.; Towe, Elias; Chamanzar, Maysamreza (Frontiers in Neuroscience, 2019)
Optical stimulation and imaging of neurons deep in the brain require implantable optical neural probes. External optical access to deeper regions of the brain is limited by scattering and absorption of light as it propagates through tissue. Implantable optoelectronic probes capable of high-resolution light delivery and high-density neural recording are needed for closed-loop manipulation of neural circuits. Micro-light-emitting diodes (µLEDs) have been used for optical stimulation, but predominantly on rigid silicon or sapphire substrates. Flexible polymer neural probes would be preferable for chronic applications since they cause less damage to brain tissue. Flexible LED neural probes have been recently implemented by flip-chip bonding of commercially available µLED chips onto flexible substrates. Here, we demonstrate a monolithic design for flexible optoelectronic neural interfaces with embedded gallium nitride µLEDs that can be microfabricated at wafer-scale. Parylene C is used as the substrate and insulator due to its biocompatibility, compliance, and optical transparency. We demonstrate one-dimensional and two-dimensional individually-addressable µLED arrays. Our µLEDs have sizes as small as 22 µm × 22 µm in arrays of up to 32 µLEDs per probe shank. These devices emit blue light at a wavelength of 445 nm, suitable for stimulation of channelrhodopsin-2, with output power greater than 200 µW at 2 mA. Our flexible optoelectronic probes are double-sided and can illuminate brain tissue from both sides of the flexible probe. Recording electrodes are co-fabricated with µLEDs on the front- and backside of the optoelectronic probes for electrophysiology recording of neuronal activity from the volumes of tissue on the front- and backside simultaneously with bi-directional optical stimulation.